2018
DOI: 10.1039/c8ra03632b
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of enhanced fluorescent copper nanoclusters encapsulated in metal–organic frameworks

Abstract: The encapsulation of Cu nanoclusters (Cu NCs) in metal–organic frameworks (MOFs) would improve the properties of Cu NCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Since different metal ions had different aggregating effects, it was worth wondering whether they were capable of transforming the irregular aggregates into regular nanomaterials here. , A-CuNCs-1 were stable in acid media at room temperature, but they would be completely decomposed after the introduction of strong alkaline such as NaOH. This was similar to the acid-stable and base-soluble behaviors of GSH and dipicolinic acid protected CuNCs. , Although NaOH could be used to dissolve A-CuNCs-1, the increase of NaOH in the colloid also significantly enhanced the pH value after the titration jump point, where the NCs would be completely broken down . Herein, a relatively weak alkaline Na 2 CO 3 was used to disperse the aggregates gently so that the generation of OH – was released by a hydrolysis route.…”
Section: Resultssupporting
confidence: 57%
“…Since different metal ions had different aggregating effects, it was worth wondering whether they were capable of transforming the irregular aggregates into regular nanomaterials here. , A-CuNCs-1 were stable in acid media at room temperature, but they would be completely decomposed after the introduction of strong alkaline such as NaOH. This was similar to the acid-stable and base-soluble behaviors of GSH and dipicolinic acid protected CuNCs. , Although NaOH could be used to dissolve A-CuNCs-1, the increase of NaOH in the colloid also significantly enhanced the pH value after the titration jump point, where the NCs would be completely broken down . Herein, a relatively weak alkaline Na 2 CO 3 was used to disperse the aggregates gently so that the generation of OH – was released by a hydrolysis route.…”
Section: Resultssupporting
confidence: 57%
“…However, the authors showed that while using tetrakis(hydroxymethyl)phosphonium chloride (THPC) as a reducing agent, not only the stability of the dihydrolipoic acid (DHLA)-stabilized cluster increases due to additional interaction with copper core, but also the PL can be tuned from red 110 to bright orange emission 111 depending on the applied reaction conditions. Other ligands such as (3mercaptopropyl)trimethoxysilane, 112 D-penicillamine, [113][114][115] cysteine, [116][117][118][119][120][121][122][123] mercaptobenzoic acid, 124,125 peptides (in particular glutathione (GSH)) 17,18,[126][127][128][129][130][131][132][133][134][135][136][137] and small organic molecules [138][139][140][141][142] were successfully applied as capping agents for the synthesis of luminescent clusters in a typical Brust-Schiffrin method ( Fig. 6).…”
Section: Modified Brust-schiffrin Techniquementioning
confidence: 99%
“…Recently, a simple one-pot synthesis of GSH-CuNC and MOF complexes (CuNCs/MOFs) was reported for the first time (Fig. 4) (Han et al 2018b). GSH-CuNCs were evenly distributed across the whole MOFs structure.…”
Section: Cu•••cu Interantionmentioning
confidence: 99%